Use of growth retardants in wheat - Espindula,M.C. (2009)
In general, lodging has been controlled by restricting nitrogen fertilizer application and/or using short cultivars. Growth retardants can also be used to solve this problem.The objective of this study was to evaluate the effect of rates and application times of three growth retardants on Pioneiro wheat cultivar. The trial was carried out in Viçosa-MG, from May to September 2005, in a factorial and hierarchical scheme, in a randomized block design with four replications and a control treatment. The treatments consisted of 500, 1,000 and 1,500 g ha-1 of chlormequat; 62.5, 125 and 187.5 g ha-1 of trinexapac-ethyl and 40, 80 and 120 g ha-1 of paclobutrazol applied at growth stages 6 or 8, growth stage used on the scale of Feeks and Large, and a control treatment without growth retardant application. Only trinexapac-ethyl and chlormequat were efficient in reducing plant height; the effect of chlormequat and paclobutrazol on plant height was independent of the application time, but the trinexapac-ethyl at growth stage 8 produced shorter plant height than at stage 6. Increasing growth retardant rates produced shorter plant heights; chlormequat and paclobutrazol did not affect grain yield. However, the highest trinexapac-ethyl rates reduced wheat yield.